Modeling resistive-inductive evolution of currents in Wendelstein 7-X - L. van Ham; S.A. Lazerson; J.C. Schmitt; B.F. Lee; M. Beurskens; K.J. Brunner; N. Chaudhary; G. Fuchert; J. Geiger; M. Hirsch; J. Knauer; A. Langenberg; et al. (Nuclear Fusion)
This research investigates the temporal evolution of the toroidal plasma current in the Wendelstein 7-X (W7-X) stellarator under different heating, fueling, and current drive scenarios. The THRIFT code has been modernized and its predictions of the evolution of the toroidal current have been compared against experimentally measured currents in W7-X. Good agreement is found with respect to the characteristic timescale between experimentally measured and simulated toroidal currents. The total bootstrap current is under-predicted owing to the applicability of the BOOTSJ model for the plasma collisionalities in question. Edge plasma resistivity is found to play an important role in the asymptotic behavior of the evolution of the current, indicating a possible limitation of the minimum plasma temperature when applying this model. Simulations of ECCD and heating power steps show THRIFT is capable of capturing the dynamical evolution of the current in response to changes in current sources. Future uses of THRIFT include validating and benchmarking other non-inductive current models.